COVID-19 Symptoms and Post Complications among Libyans - Hafsa A. Alemam; Mofida M. Alfaid; Mohamed Aljabri; Zuhur Lahrsh; Manal Khalifa Hasan; Hajer M Almuaket; Abdounasser Albasher Omar (African Journal of Advanced Pure and Applied Sciences, 2024)
The battle against COVID-19 does not always end when recovery is declared. Many individuals confirmed recovered from COVID-19 continue to experience a variety of symptoms. The aim of this study was to shed more light on COVID-19 and post-COVID-19 symptoms in Libya. Two hundred and twenty Libyan individuals (58% female; 42% male), who recovered from COVID‐19, were asked to answer a questionnaire that was performed to inquire about the presence of COVID-19 and post-COVID-19 symptoms. Additionally, comorbidities and demographic data were included. The most common comorbidities were hypertension (20%), diabetes (16%), and lung disease (08%). The main COVID-19 symptoms were headache (56%), anosmia and ageusia (52%), Arthralgia (48%), cough (46%) and fever (41%). While the post-COVID-19 symptoms were fatigue (64%), sleep disorders (52%), insomnia, anxiety, depression (42%), and anosmia and ageusia (32%). Persistent COVID and its related long-term complications may continue to affect patients and their families.